The definitive guide to SOA : Oracle Service Bus - Davies, Jeff (Jeff Michael) (Expert's voice in SOA., 2008)
"This book provides hands-on information to developing SOA-driven applications with ESBs as central components. It also gives strategic guidance on SOA planning, web service life-cycle management, administration of an ESB, and security considerations. Author Jeff Davies is careful to cut through theory and get straight to demonstrating successful use of the product."--Jacket